The impact of human resource management practices on employee engagement - Habibah, Othman (2019)
This research paper is to present the findings on the influence of rewards and recognition, training and development and performance appraisal (human resource management practices) on employee engagement at a well-established Property Management Company located in Kuala Lumpur. The information was collected by questionnaire distribution to one of the property management company and total numbers of workers responded was 150. The respondents were from non-executives and executives’ level. The data was analyzed using Statistical Package for Social Science (SPSS). The relationship between the variables has been analyzed using multiple regression. Hence, the finding of this study revealed that there is a significant relationship between human resource practices (rewards and recognition as well as training and development) with employee engagement. However, there is no significant relationship for performance appraisal with employee engagement. The findings give an insightful information and guidance for researchers and practitioners to identify solutions that can help to improve human resource practices at the workplace.